The Perspective of Non-oncologist Physicians on Patients with Metastatic Cancer and Palliative Care (ALONE Study): A Study of the Palliative Care Working Committee of the Turkish Oncology Group (TOG) - (:unkn) unknown (SPRINGER, 2015)
The aim of our study was to determine the perspective of non-oncologist physicians regarding their attitudes and beliefs associated with palliative care for patients with metastatic cancer. The study was planned as a cross-sectional survey, and non-oncologist physicians were reached via e-mail and social networking sites. The first part of the questionnaire involved demographic properties, the second part inquired as to the perspectives of participants regarding metastatic disease, and the third part was used to determine beliefs and attitudes about palliative care. All of the questions were five-point Likert-type questions. A total of 1734 physicians completed the questionnaire. The majority of participants were general surgeons or internal medicine specialists (21 and 18 %, respectively), were male (61 %), were younger than 50 years of age (54 %), worked in the town center (67 %), had more than 11 years of professional experience (57 %), and worked in a hospital without an active oncology service (86 %). A total of 71 % of participants identified all patients with metastatic cancer as being terminal stage, 62 % were unaware of palliative care techniques, 64 % did not know about common supportive care options, 59 % were against hospice, and 63 % had no opinion on resuscitation. We determined that non-oncologist physicians believed that all patients with metastatic cancer are at the terminal stage and that palliative/supportive care is the oncologist's task. These data suggest that non-oncologist physicians would benefit from additional graduate and postgraduate courses on these topics.
Keywords: Physicians; Palliative care; Best supportive care; Cancer; Metastatic disease; Terminal stage cancer; KNOWLEDGE; ATTITUDES; TURKEY